Case Report: Recurrent acute myocardial infarction in a young woman—the importance of identifying the uncommon underlying causes - Hong Zhi; Chengyi Xu; Hua Yan; Chengwei Liu; Li Liu (Frontiers in Cardiovascular Medicine)
Studies have shown that the occurrence and mortality of ischemic heart disease (IHD) in young women aged 35–54 years have increased despite improving trends globally among the general population. Common risk factors such as hypertension, hyperlipidemia, diabetes and smoking play an important role in the occurrence of IHD, but some rare causes that are easily misdiagnosed or undiagnosed should also be paid attention to. Here, we report the case of a young woman (33 years old) who suffered from recurrent acute myocardial infarction (AMI) and was ultimately diagnosed with Turner syndrome (TS) by karyotype testing. TS was identified as the cause of IHD in this patient. We then adjusted treatment strategy to include long-term estrogen-progestin therapy in addition to conventional treatment for IHD (e.g., anti-platelet, lipids-lowering). The patient has been followed up on an outpatient basis and is in good clinical condition. In this report, we highlighted the important of identifying rare causes when treating young women with IHD, and we also discussed the guideline management in such patients.